2003
DOI: 10.1002/ijc.11252
|View full text |Cite
|
Sign up to set email alerts
|

Expression of tumor markers hyaluronic acid and hyaluronidase (HYAL1) in head and neck tumors

Abstract: Characteristic behaviors of head and neck squamous cell carcinoma (HNSCC) include a propensity to occur as multiple synchronous and metachronous tumors, frequent recurrence and metastasis. Early detection of HNSCC and monitoring its recurrence are necessary to improve prognosis. Hyaluronic acid (HA), a component of extracellular matrix, promotes metastasis. Small fragments of HA stimulate angiogenesis. HA fragments are generated when hyaluronidase (HAase), an endoglycosidase, degrades the HA polymer. Using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
114
4
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 54 publications
1
114
4
1
Order By: Relevance
“…HA (i.e., HA fragments) species are present in the saliva of high-stage head-and-neck squamous cell carcinoma patients but not in the saliva of normal individuals. 8 Taken together, our findings and those of Dr. Kumar's group show that, in addition to the increased amounts of HA in cancer patients' body fluids (i.e., urine, serum and saliva) and tumor tissues, the size profile of HA species may be important in cancer diagnosis and for evaluating the biologic behavior of various tumors.…”
supporting
confidence: 75%
“…HA (i.e., HA fragments) species are present in the saliva of high-stage head-and-neck squamous cell carcinoma patients but not in the saliva of normal individuals. 8 Taken together, our findings and those of Dr. Kumar's group show that, in addition to the increased amounts of HA in cancer patients' body fluids (i.e., urine, serum and saliva) and tumor tissues, the size profile of HA species may be important in cancer diagnosis and for evaluating the biologic behavior of various tumors.…”
supporting
confidence: 75%
“…Altered expression profiles of the Hyal and HAS proteins have been associated with many types of cancers (3)(4)(5)(6)(7). Detection of elevated expression of Hyal1 and concurrent accumulation of HA in biopsies are an indicator of poor prognosis for prostate cancer (8).…”
mentioning
confidence: 99%
“…[54] Also, previous few studies reported high levels of in HNSCC. [55,56] In contrast, the HA expression is low in melanoma, and its absence is significantly correlated with the metastatic potential. [57,58] Accumulation of HA can decrease tumorigenic potential and confer resistance to cancer.…”
Section: Discussionmentioning
confidence: 99%